Kajian Komprehensif Penerapan Ergonomi di Berbagai Sektor Kerja di Indonesia - Tri Wahyu Setyawati; Hernadewita; Anwaruddin Yusuf; Hassan Fathuramdhan Wijaya (Jurnal Serambi Engineering, 2025)
This literature review synthesizes findings from 20 recent studies that apply ergonomic principles and methods in various work contexts in Indonesia. These studies highlight the importance of ergonomics in optimizing human well-being and system performance, as well as addressing problems such as discomfort, fatigue, decreased productivity, and the risk of musculoskeletal disorders (MSDs). This review identifies common approaches such as postural risk assessment methods (REBA, NBM, ROSA) and physical redesign interventions. The results from the application of ergonomics consistently demonstrate positive outcomes, including a reduction in MSDs risk and increased productivity. This review also highlights research gaps, including the lack of focus on cognitive and organizational ergonomics, longitudinal studies, cost-benefit analysis, and the implementation of real-time technology. Future research is suggested to explore more integrated and to guarantee the establishment of an ergonomic and risk-free work environment in Indonesia.